The Influence of Abnormalities in the Profile and Overjet on Psychological Well-Being - Emine Kaygısız; Ayşe Bikem Hacıömeroğlu; Sema Yüksel; Mümin Mümin; Tuba Tortop (Galenos Yayinevi, 2021)
Objective:This study aimed to comparatively evaluate the psychological well-being and health-related quality of life of subjects having either a convex or concave profile and abnormal overjet, with subjects having a straight profile and normal overjet.Methods: In this study, 163 children and their parents who applied to the Faculty of Dentistry were classified into 3 groups: Group 1: convex profile, Class II molar relationship, and increased overjet (n=62; 28 boys and 34 girls; mean age: 11.6 years); Group 2: concave profile, Class III molar relationship, and negative overjet (n=55; 32 boys and 23 girls; mean age: 11.2 years); and Group 3: straight profile, Class I molar relationship without crowding, and normal overjet (n=46; 24 boys and 22 girls; mean age: 11.0 years). The severity of malocclusion was evaluated using the Index of Orthodontic Treatment Need (IOTN). Self-concept, depression, and state-trait anxiety were evaluated to determine the psychological well-being of the children.Results: No differences were found among the groups with respect to self-concept, depression levels, state-trait anxiety levels, and quality of life scores. No correlation was found between the IOTN scores and psychological well-being.Conclusion: Abnormalities in the facial profile and negative or increased overjet have no influence on children's psychological well-being.